N-acetylcysteine reduces prefrontal reactivity to cocaine cues in individuals with cocaine use disorder - Engeli, Etna J. E.; Preller, Katrin H.; Rieser, Nathalie M.; Klar, Johanna; Staempfli, Philipp; Hulka, Lea M.; Kirschner, Matthias; Seifritz, Erich; Herdener, Marcus (Frontiers in Psychiatry, 2025)
BackgroundIndividuals with cocaine use disorder experience heightened motivation to pursue rewards tied to cocaine, often triggered by associated cues. Cue reactivity and subsequent craving significantly elevate the risk of substance use, creating a pressing need for treatments that can help alleviate cravings. However, no pharmaceutical therapies for treating cocaine use disorder have been approved. Preclinical findings reveal dysfunctions in the glutamatergic pathway connecting prefrontal regions with the nucleus accumbens, which are correlated with cue-induced substance-seeking behaviour. These alterations, at both molecular and behavioural levels, can be reversed in rodents with N-acetylcysteine, a modulator of glutamatergic signalling. In contrast, the therapeutic potential for humans remains uncertain.MethodsHere, we assessed the impact of a short-term challenge with N-acetylcysteine on neural responses to cocaine cues and cue-induced craving in a randomised, placebo-controlled cross-over trial using a fMRI cue reactivity paradigm. In total, 44 fMRI cue reactivity scans of 22 individuals with cocaine use disorder were recorded—once after the administration of 2,400 mg of N-acetylcysteine/day for 2 days and once after placebo intake.ResultsIn the placebo condition, participants showed increased cue reactivity towards cocaine pictures, accompanied by significantly higher cravings as compared to neutral images. In accordance with recent meta-analyses, cue reactivity was evident in parietal regions such as the posterior cingulate and precuneus, temporal regions like the hippocampus, the bilateral insula, and medial prefrontal regions, namely the inferior, middle, and superior frontal gyrus. Cue-induced activity in the superior frontal gyrus was strongly predicted by the individual duration of cocaine use. While N-acetylcysteine showed no impact on subjectively rated cocaine craving, neural cue reactivity in the superior frontal gyrus was significantly decreased under N-acetylcysteine compared to placebo.ConclusionsOur findings show that prefrontal reactivity to cocaine cues can be reduced even by a brief pharmacological challenge with N-acetylcysteine. Since neural drug cue reactivity has been shown to be a precursor of relapse behaviour, N-acetylcysteine’s therapeutic potential should be further investigated in future studies by extending treatment periods.Clinical Trial Registrationhttps://clinicaltrials.gov, identifier NCT02626494.